China's resource insecurity from iron ore perspective : a comparative analysis between Japan and China. - Zhou, Longquan. (2013)
Iron ore, as the crucial raw material of steel making, playsa vital role in the global resources market. Since 2003, China has become the largest importer of it. As a result of the soaring price of iron ore, China is stuck in a passive position. Nonetheless, being a fellow importer, Japan does not suffer a lot from the similar situation.